2013
DOI: 10.1038/cr.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-3p regulates the formation and differentiation of hematopoietic stem cells in vertebrates

Abstract: Previous studies on developmental hematopoiesis have mainly focused on signaling and transcription factors, while the appreciation of epigenetic regulation including that of microRNAs is recent. Here, we show that in zebrafish and mouse, miR-142-3p is specifically expressed in hematopoietic stem cells (HSCs). Knockdown of miR-142a-3p in zebrafish led to a reduced population of HSCs in the aorta-gonad-mesonephros (AGM) region as well as T-cell defects in the thymus. Mechanistically, miR-142a-3p regulates HSC fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 44 publications
(66 reference statements)
4
75
1
Order By: Relevance
“…Our conclusion is in agreement with observations by others that miR-142-3p and not miR-142-5p is responsible for the regulation of immune cell function in mice 12,13,35 and zebrafish. [9][10][11] Growing evidence suggests that miRNAs tightly control cellular responses and organismal homeostasis by targeting signaling nodes in a variety of physiological networks. In agreement with this notion, our study shows that miR-142-3p targets several signaling pathways that play well-established roles in B-cell differentiation and function, including the VDJ recombination complex, actin cytoskeleton rearrangement networks, and BAFF-R signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our conclusion is in agreement with observations by others that miR-142-3p and not miR-142-5p is responsible for the regulation of immune cell function in mice 12,13,35 and zebrafish. [9][10][11] Growing evidence suggests that miRNAs tightly control cellular responses and organismal homeostasis by targeting signaling nodes in a variety of physiological networks. In agreement with this notion, our study shows that miR-142-3p targets several signaling pathways that play well-established roles in B-cell differentiation and function, including the VDJ recombination complex, actin cytoskeleton rearrangement networks, and BAFF-R signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of miR-142-3p expression in zebrafish revealed a critical role for this miRNA in hematopoiesis during embryonic development, hematopoietic stem cell homeostasis, neutrophil differentiation, and heart development. [9][10][11] In mice, miR-142 is essential for normal development and function of megakaryocytes, dendritic, and mast cells.…”
Section: Introductionmentioning
confidence: 99%
“…North American eastern equine encephalitis virus (EEEV) has a single-stranded sense RNA genome and can cause fatal infections in humans (5). miR-142-3p is a hematopoietic-cell-specific miRNA (65) which is involved in specification, formation, and differentiation of hematopoietic stem cells (70,71), macrophage differentiation (72), proliferation and differentiation of mesenchymal cells in lungs (73), proliferation of CD25 ϩ CD4 T cells (74), and the migration of CD4 T cells (75). miR-142-3p binds three highly conserved target sites in the 3= UTR of the EEEV genomic RNA, thereby potently restricting EEEV in myeloid-lineage cells by blocking viral translation and subsequent replication (76).…”
Section: The Hijackermentioning
confidence: 99%
“…Previous studies in mice showed that cytokines including interleukin-1 (IL-1) and IL-3 are involved in the embryonic development of HSPCs in the aorta-gonad-mesonephros (AGM) region. 15,16 We previously reported that a hematopoietic microRNA, miR-142a-3p, regulates the formation and differentiation of HSPCs by regulating the inflammatory signaling cascade irf7-gcsfr, 17 indicating a possible role of inflammatory signaling in HSPC emergence. In this study, we demonstrated that in both zebrafish and mouse embryos, inflammatory signaling is required for HSPC specification.…”
Section: Introductionmentioning
confidence: 99%